2005
DOI: 10.3928/01484834-20051001-07
|View full text |Cite
|
Sign up to set email alerts
|

A Service Learning Research Methods Course

Abstract: Incorporation of service learning into an undergraduate nursing research course has the potential to invigorate baccalaureate nursing students' interest in research through real-world connections. In this article, I describe the development and implementation of an undergraduate nursing research course that incorporated service learning. The course experience proved to be enlightening for both the students and instructor, and propelled students to continue their research beyond the course requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The majority of papers found addressed mental health, and although the bulk of these papers provided only programme descriptions (Stocking and Cutforth, ; Beltran et al , ; Lashley, ; Raiz, ), some of the publications provided quantitative and/or qualitative outcomes assessing students' knowledge, skills and attitudes (Coates and Crist, ; Flinn et al , ; Atler and Gavin, ; Schindler, ). Fewer publications addressed research skills, and the majority of these were limited to programme descriptions (Brosnan et al , ; Rash, ; Portney and Applebaum, ; Strand, ; Schindler, ). Two publications indicated that nursing students in community engagement programmes expressed greater motivation and enthusiasm for learning research in comparison with students in a traditional research curriculum (Peterson and Schaffer, ; Balakas and Sparks, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of papers found addressed mental health, and although the bulk of these papers provided only programme descriptions (Stocking and Cutforth, ; Beltran et al , ; Lashley, ; Raiz, ), some of the publications provided quantitative and/or qualitative outcomes assessing students' knowledge, skills and attitudes (Coates and Crist, ; Flinn et al , ; Atler and Gavin, ; Schindler, ). Fewer publications addressed research skills, and the majority of these were limited to programme descriptions (Brosnan et al , ; Rash, ; Portney and Applebaum, ; Strand, ; Schindler, ). Two publications indicated that nursing students in community engagement programmes expressed greater motivation and enthusiasm for learning research in comparison with students in a traditional research curriculum (Peterson and Schaffer, ; Balakas and Sparks, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 7 ] Training for research skills and experience of research in an early time in the medical profession is associated with continued professional academic work and may also help resident's career decisions. [ 7 ] While many undergraduate programs include research methodology course,[ 8 ] medical training in many developing countries does not emphasize its importance in medical practice and this course is not included in the medical curriculum. [ 7 ] Compulsory research course along with a mandatory research project has a positive impact on student's knowledge and attitudes toward research.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward the idea of reading research may also be biased by a statistics/math phobia (O'Connor & O'Neill, 2004;Sternberger, 2002). As has been described by Rash (2005), a research course "…is seldom a course students eagerly anticipate" (p. 477).…”
Section: Factors Contributing To Students' Attitudes Toward Researchmentioning
confidence: 99%
“…Over the past two decades, nursing program research course instructional approaches have moved from predominantly didactic approaches such as lecture and individual written assignments to more small group and experiential learning. For example, today nursing students can complete their own small research projects, collaborate with clinicians to develop and address practice-based questions (e.g., see August-Brady, 2005;Kenty, 2001;McCurry & Martins, 2010;Rash, 2005); work on existing faculty projects (e.g., Mandleco & Schwarz, 2002), and participate in pseudo research projects as a learning process. This imncludes the "cookie experiment", as first described by Thiel (1987), expanded by Morrison-Beedy and Côté-Arsenault (2000), adapted to be based on a music intervention suitable for use with distance students (Sternberger, 2002), and still found to be useful (Meeker, Jones & Flanagan, 2008).…”
Section: Factors Contributing To Students' Attitudes Toward Researchmentioning
confidence: 99%